Diagnosis and Treatment of Spinal Syphilitic Gumma: A Case Report - Cui, Linyang; Xu, Zushan; Hou, Hongjun (Frontiers in Neurology, 2020)
Neurosyphilis, which is caused by Treponema pallidum, is a rare sexually transmitted disease involving the central nervous system (CNS). Among all the sub-categories, spinal syphilitic gumma is extremely rare. In previous literature, limited cases of spinal syphilitic gumma have been reported, most of which underwent surgery treatment. In this study, we reported a 46-year-old man, who presented with 5-day numbness of bilateral lower limbs, lower back pain, and irregular defecation. Magnetic resonance imaging (MRI) revealed a homogeneous peripheral enhancement and intramedullary nodule at the T7 level with extensive thoracic cord edema. Combining with laboratory examination results, the syphilitic gumma was considered. One month after the administration of penicillin G, the symptoms vanished. Six months later, MRI indicated no intramedullary nodule.